2021
DOI: 10.1021/acs.jpcb.1c05156
|View full text |Cite
|
Sign up to set email alerts
|

Transferable Gaussian Attractive Potentials for Organic/Oxide Interfaces

Abstract: Organic/oxide interfaces play an important role in many areas of chemistry, and in particular for lubrication and corrosion. Molecular dynamics simulations are the method of choice for providing complementary insight to experiments. However, the force fields used to simulate the interaction between molecules and oxide surfaces tend to capture only weak physisorption interactions, discarding the stabilizing Lewis acid/base interactions. We here propose a simple complement to the straightforward molecular mechan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 101 publications
0
15
0
Order By: Relevance
“…Instead of system-specific tuning of parameters, several research groups have pushed for hybrid solvation schemes, where the (surface) reactions are described at the density functional theory (DFT) level and the solvent effects are captured by molecular mechanics (MM). MM is many orders of magnitude less expensive than DFT, and therefore, extensive phase-space sampling of the liquid is easily in reach. Furthermore, compared to implicit solvents, it is clearer how to improve the quality of the description of the interface energetics: Force fields can be tested against DFT and system-specifically improved. , As an example, we have shown that a purpose-built force field for the interaction of water with the Pt(111) surface leads to a semiquantitative agreement with experiment for the adsorption of phenol and benzene on Pt(111), while the standard implicit solvent gives qualitatively wrong results when comparing the adsorption in the gas phase with adsorption in the liquid . Similarly, good agreement between DFT and MM solvation energies has been achieved at the alumina/water interface .…”
Section: Introductionmentioning
confidence: 87%
“…Instead of system-specific tuning of parameters, several research groups have pushed for hybrid solvation schemes, where the (surface) reactions are described at the density functional theory (DFT) level and the solvent effects are captured by molecular mechanics (MM). MM is many orders of magnitude less expensive than DFT, and therefore, extensive phase-space sampling of the liquid is easily in reach. Furthermore, compared to implicit solvents, it is clearer how to improve the quality of the description of the interface energetics: Force fields can be tested against DFT and system-specifically improved. , As an example, we have shown that a purpose-built force field for the interaction of water with the Pt(111) surface leads to a semiquantitative agreement with experiment for the adsorption of phenol and benzene on Pt(111), while the standard implicit solvent gives qualitatively wrong results when comparing the adsorption in the gas phase with adsorption in the liquid . Similarly, good agreement between DFT and MM solvation energies has been achieved at the alumina/water interface .…”
Section: Introductionmentioning
confidence: 87%
“…Alternatively, MM atoms at the QM/MM boundary can be replaced by pseudopotentials 32 . However, parameterising force-fields to match the energetics of the QM and MM regions more reliably reduces the energetic discontinuity without introducing additional corrective potentials [43][44][45] .…”
Section: Force-field Parameterisationmentioning
confidence: 99%
“…31 However, parameterising force-fields to match the energetics of the QM and MM regions more reliably reduces the energetic discontinuity without introducing additional corrective potentials. 42–44…”
Section: Basics Of Qm/mmmentioning
confidence: 99%
See 1 more Smart Citation
“…This MMSolv strategy has been validated against experimental data on the adsorption of aromatics at the Pt/water interface. MMSolv performs noticeably better than PCM thanks to a proper inclusion of the surface solvation. It can be easily used with oxides surfaces, given that the chemisorption of water is well described . When considering the adsorption of flexible molecules (e.g., polyols), MMsolv can be combined with our package DockOnSurf to automate the sampling of conformers.…”
mentioning
confidence: 99%